2023
DOI: 10.3389/fenvs.2023.1153601
|View full text |Cite
|
Sign up to set email alerts
|

Increasing precipitation promoted vegetation growth in the Mongolian Plateau during 2001–2018

Abstract: Taking the Mongolian Plateau as the research area, this paper studied the vegetation growth from 2001 to 2018. We quantified the vegetation growth changes based on changes in gross primary productivity (GPP) and leaf area index (LAI) and their relationships to climate variables using correlation analysis, partial correlation analysis and multiple correlation analysis. The results showed that from 2001 to 2018 both GPP and LAI showed an increasing trend, with great heterogeneities among different areas and land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 62 publications
0
0
1
Order By: Relevance
“…Contrary to our expectation, our results showed that precipitation amount explained little to the year-by-year increase in NDVI, even in the area where vegetation growth is traditionally constrained by precipitation. Previous studies often suggested that annual precipitation amount or GSP was the predominant climatic factor controlling the spatial or temporal variations in primary production in arid grassland ecosystems [14,38,[46][47][48], although productivity was always less sensitive to precipitation in temporal models than that in spatial models [17,18,49]. However, here, we found that previous models do not always work in understanding the year-by-year changes in NDVI, in which NDVI increases significantly without the increase or even decrease in GSP over years.…”
Section: Increased Precipitation Amount Was Not Significantly Respons...contrasting
confidence: 58%
“…Contrary to our expectation, our results showed that precipitation amount explained little to the year-by-year increase in NDVI, even in the area where vegetation growth is traditionally constrained by precipitation. Previous studies often suggested that annual precipitation amount or GSP was the predominant climatic factor controlling the spatial or temporal variations in primary production in arid grassland ecosystems [14,38,[46][47][48], although productivity was always less sensitive to precipitation in temporal models than that in spatial models [17,18,49]. However, here, we found that previous models do not always work in understanding the year-by-year changes in NDVI, in which NDVI increases significantly without the increase or even decrease in GSP over years.…”
Section: Increased Precipitation Amount Was Not Significantly Respons...contrasting
confidence: 58%